Ethnic density and area-deprivation effects on central obesity among ethnic minority people in England—A cross-sectional, multi-level analysis - Higgins, Vanessa (Frontiers in Epidemiology, 2022)
Background Central obesity is a risk factor for many health conditions, and it disproportionately affects some ethnic minority groups. Research has shown that there is an association between area environments and obesity, but no studies have explored the association between co-ethnic density and central obesity in the UK (United Kingdom). This paper addresses the following research question: Does the relationship between co-ethnic density/area deprivation and waist circumference differ by ethnic group in England? Methods Data come from four years of the cross-sectional Health Survey for England (1998, 1999, 2003, 2004) and linked area-level data from the 2001 Census. More recent data on objectively measured central obesity for a nationally representative sample of ethnic minorities does not exist. Multi-level modelling methods account for individual-level and area-level factors. Interaction models test the effect of area deprivation and co-ethnic density for each ethnic group compared with the White reference group. Results For women, the relationship between area deprivation and waist circumference does not vary by ethnic group. For Indian and Bangladeshi men there is a decrease in waist circumference as area deprivation increases. There is an increase in waist circumference as co-ethnic density increases for Black Caribbean women. For Indian men there is a decrease in waist circumference as co-ethnic density increases. Conclusions Further research is needed to understand the mechanisms through which (1) increasing area-deprivation is protective for Indian and Bangladeshi men and (2) increasing co-ethnic density is associated with an increase in waist circumference for Black Caribbean women but a decrease in waist circumference among Indian men. Each of these results are important because (1) Indian and Bangladeshi men have an increased risk of the metabolic syndrome, which is linked to central obesity, and (2) Black Caribbean women have a higher risk of central obesity than the general population in England.